Crunch - Connor, Leslie (Katherine Tegen Books, 2012)
The oldest Marriss brother, fourteen-year-old Dewey, attempts to be the "embodiment of responsibility" as he juggles the management of the family's bicycle repair business while sharing the household and farm duties with his siblings after a sudden energy crisis strands their parents far from home.